2005
DOI: 10.1002/hbm.20127
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the inferior frontal junction in cognitive control: Meta‐analyses of switching and Stroop studies

Abstract: There is growing evidence that a specific region in the posterior frontolateral cortex is involved intimately in cognitive control processes. This region, located in the vicinity of the junction of the inferior frontal sulcus and the inferior precentral sulcus, was termed the inferior frontal junction (IFJ). The IFJ was shown to be involved in the updating of task representations and to be activated commonly in a within-subject investigation of a task-switching paradigm, the Stroop task, and a verbal n-back ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
479
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 549 publications
(553 citation statements)
references
References 63 publications
67
479
3
4
Order By: Relevance
“…The role of the IFJ in WM and cognitive control: Uploading relevant rule information As we mentioned before, studies have shown the IFJ to be crucially involved in cognitive control and, more specifically, in task switching (Brass and von Cramon, 2002, 2004a, 2004bBrass et al, 2005;Derrfuss et al, 2005;Dove et al, 2000;Kim et al, 2012;Sylvester et al, 2003). Studies have also observed the IFJ to be involved in interference control and updating (e.g., Braver et al, 1997;de Fockert et al, 2004;Derrfuss et al, 2004Derrfuss et al, , 2005Mead et al, 2002;Roth et al, 2009;Sylvester et al, 2003).…”
Section: The Nature Of Wm Resources: Domain-general Time-based Resourmentioning
confidence: 91%
See 3 more Smart Citations
“…The role of the IFJ in WM and cognitive control: Uploading relevant rule information As we mentioned before, studies have shown the IFJ to be crucially involved in cognitive control and, more specifically, in task switching (Brass and von Cramon, 2002, 2004a, 2004bBrass et al, 2005;Derrfuss et al, 2005;Dove et al, 2000;Kim et al, 2012;Sylvester et al, 2003). Studies have also observed the IFJ to be involved in interference control and updating (e.g., Braver et al, 1997;de Fockert et al, 2004;Derrfuss et al, 2004Derrfuss et al, , 2005Mead et al, 2002;Roth et al, 2009;Sylvester et al, 2003).…”
Section: The Nature Of Wm Resources: Domain-general Time-based Resourmentioning
confidence: 91%
“…More specifically, we examined the pattern of activation in the left and right IFJ. Importantly, these ROIs were defined independently from the aforementioned analyses by using the coordinates for the IFJ as reported in the meta-analysis of Derrfuss et al (2005). The coordinates were converted into MNI coordinates using GingerALE.…”
Section: Regions Of Interest Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Structure-based and BA-based searches are unsatisfactory because nearby activations might receive different anatomical labels or different BA designations, and activations quite distant from one another might be given identical anatomical labels or BA designations. For example, activations close to the junction of the inferior frontal sulcus and the inferior precentral sulcus Derrfuss et al, 2004Derrfuss et al, , 2005Derrfuss et al, , 2009) might be referred to as lying in the inferior precentral sulcus, the inferior frontal sulcus, the precentral gyrus, the middle frontal gyrus, the inferior frontal gyrus, pars opercularis, Broca's area, the premotor cortex, or the inferior frontal junction. On the other hand, activations in the most ventral and the most dorsal part of the posterior frontal cortex might both receive the label "precentral gyrus" or "BA 6," although these activations might lie as far as 60 mm apart.…”
Section: How Can We Go About Finding These Studies?mentioning
confidence: 99%